Understanding Homelessness in Neoliberal City: A Study from Delhi. (March 2020) - Ghosh, Subhamay
'Homelessness' is the worst form of urban poverty, and in the wake of neoliberalism it has become more pervasive in cities across the world. Taking the case of Delhi, the study focuses on the making of homelessness, the connotation of being homeless, and the nature of responses from a governing institution to homelessness in the neoliberal city. The study reveals that large scale slum demolition in the last three decades has rendered thousands of people homeless. They are denied of basic human rights and human necessities. They are not even allowed to reside in the open spaces of the city. Governing actors have bypassed their duties by setting up only a 'few' night-shelters in the city, most of which remained unoccupied because of several adversities. The study also reveals that homelessness is the outcome of governance failure and the failure of the welfare state. But the structural problem of homelessness is completely overlooked both in policy and by 'other' sections of society.